2023
DOI: 10.1021/acscatal.2c06016
|View full text |Cite
|
Sign up to set email alerts
|

Carbocation-Catalyzed Intramolecular and Intermolecular Carbonyl-Alkyne Metathesis Reactions

Abstract: The carbonyl-alkyne metathesis (CAM) reaction is a versatile, stereoselective, and atom-economical method to access a diverse range of α,βunsaturated carbonyl compounds, which are useful synthetic precursors and constitute an important structural motif in biologically active substances. In this work, we developed an efficient organic Lewis acid catalytic system to promote both the intramolecular and intermolecular CAM reactions. This type of versatile catalytic activity has been rarely demonstrated for other e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The following supporting information is available: general experimental information, synthetic procedures and characterization of isolated compounds, additional experimental and DFT data, copies of NMR spectra and crystallographic data in CIF or other electronic format see: DOI:10.1002/###.20230XXX. The following additional references have been cited within the Supporting Information [41–77] …”
Section: Supporting Informationmentioning
confidence: 99%
“…The following supporting information is available: general experimental information, synthetic procedures and characterization of isolated compounds, additional experimental and DFT data, copies of NMR spectra and crystallographic data in CIF or other electronic format see: DOI:10.1002/###.20230XXX. The following additional references have been cited within the Supporting Information [41–77] …”
Section: Supporting Informationmentioning
confidence: 99%
“…A general mechanism is proposed on the basis of these observations and prior literature (Scheme ). The 18 O labeling experiment demonstrated that 16 O/ 18 O exchange via CO migration from 1a′ to Ru 3 (CO) 12 is accessible, and subsequent CO migration from Ru 3 (CO) 12 to 1c occurs to give 18 O labeling product 3ca .…”
mentioning
confidence: 93%
“…The reaction between 1H-indene-1,2,3-trione (1a) and methyl(phenylethynyl)sulfane (4a) was also evaluated (Table S2) and progressed smoothly after replacing Ru 3 (CO) 12 with CoCl 2 at 130 °C, thereby producing the desired product 5aa in 89% yield (Table 2). To our delight, no corresponding cyclization product was observed under Co-catalyzed conditions.…”
mentioning
confidence: 99%
“…Based on our earlier works [16] on olefination of carbonyl compounds [17] via carbonyl‐olefin metathesis, [18] we envisioned that ketals of cyclic ketones II could be suitable substrates for a Brønsted acid catalyzed cascade enolization‐[2+2]cycloaddition‐[2+2]cycloreversion sequence with another carbonyl compound I to form the corresponding ring‐opening ester products (Scheme 1a). Oxetanium III is a frequently encountered intermediate in carbonyl chemistry [16a–e,19] . Key to this cascade sequence is the enolization of the cyclic ketal under acidic conditions, [18j] which releases a ‘hemiketal enol ether’ reactive intermediate II′ for a [2+2]cycloaddition reaction [20] specifically at the newly created C−C double bond.…”
Section: Introductionmentioning
confidence: 99%